Problems of Formation of Phonetic Competence of Students (A Level 1) - Akhmedova Adolat Ravshan kizi (Genius Publishing Group, 2022)
This article deals with the formation of students' phonetic competence (level A 1).
Keywords: Foreign language; German; CEFR; listening